Modified Extracorporeal Septoplasty: Functional Results at 6-Year Follow-up. Issue 5 (May 2016) - Persichetti, Paolo; Toto, Vito; Segreto, Francesco; Signoretti, Matteo; Marangi, Giovanni Francesco
Abstract : Background: Septal deviations represent a major cause of aesthetic disorders and respiratory obstruction. The traditional septoplasty techniques may often be inadequate to treat severe deviations. Recently, we described a modified extracorporeal septoplasty approach based on partial resection of the cartilaginous septum, with preservation of a superocaudal L-strut measuring approximately 0.5 cm in height. At 6-month follow-up, we demonstrated this technique to be functionally and aesthetically effective in addressing mild to severe septal deviation. The aim of the present study was to evaluate the long-term outcomes of this technique in the patients included in the initial prospective study, followed up during a period of 4 to 6 years. Methods: One hundred fifty-three patients underwent modified extracorporeal septoplasty from January 2006 to June 2009. One hundred twenty of these patients were included in the present study. Patients were grouped according to the preoperative septal deviation as follows: mild (one-third reduction of the nasal cavity), moderate (half reduction), and severe (two-thirds reduction). Follow-up ranged from 4 to 6 years. Respiratory flow improvement was assessed with active anterior rhinomanometry; subjective evaluation of the respiratory function was obtained by mean of Nasal Obstruction Symptom Evaluation (NOSE) scale. Active anterior rhinomanometry values and NOSE scores were compared with the results obtained preoperatively and at 6-month postintervention. Results: In the whole cohort, rhinomanometric analyses and NOSE scores at long-term follow-up demonstrated a statistically significant improvement in inspiratory flow and obstructive symptoms ( P = 0.0122 and P < 0.0001, respectively) compared to preoperative values. In group analysis, a significant improvement in NOSE scores was found in patients with severe ( P < 0.0001) and moderate ( P < 0.0001) deviations. A significant improvement in inspiratory flow was reported in the severe ( P < 0.0001) and moderate ( P = 0.0212) deviation groups. Conclusions: The modified extracorporeal septoplasty technique proved to be functionally effective at long-term follow-up in cases of moderate or severe septal deviation: the improvements in respiratory function and obstructive symptoms found 6 months postoperatively were maintained at 4 to 6 years postintervention. With this technique, structural support is achieved without destabilizing the keystone area; moreover, conservative remodeling of the quadrangular cartilage allows the use of septal cartilage grafts in secondary or revision rhinoplasty.